Policy Regulation of Precarious Work Schedules and Bottom-Up Enforcement: An Evaluation of State Reporting Pay Policies. - Finnigan, Ryan; Hunter, Savannah (Social Forces, 2022)
Precarious work schedules, including last-minute cuts to workers' shifts, undermine well-being for millions of workers and their families in the United States. Drawing on dispute resolution theories and prior research on complaint-driven enforcement of labor regulations, this study evaluates whether and how labor regulations can moderate this precarity. In eight states and Washington, DC, "reporting pay" policies require employers to pay workers for some portion of their shift if they report to work but the employer ends their shift much earlier than scheduled. To evaluate these policies, we fielded an original survey of hourly workers measuring self-reported and actual policy coverage, the frequency of shift cuts, and receipt of reporting pay following shift cuts. We find evidence for only partial compliance with reporting pay policies, at best. We next examine the role of workers' information about these policies in the enforcement process. Extremely few workers covered by reporting pay policies accurately identified the presence of the state policy. However, a survey experiment demonstrates that providing information about reporting pay policies significantly increases recommendations that a hypothetical worker should push for compensation for a shift cut, either with the manager directly or through external enforcement by the state. We conclude with discussion of bottom-up enforcement for labor regulations and possibilities for improvement.